Trunk and lower limb coordination during lifting in people with and without chronic low back pain. (11th April 2018) - Pranata, A.; Perraton, L.; El-Ansary, D.; Clark, R.; Mentiplay, B.; Fortin, K.; Long, B.; Brandham, R.; Bryant, A.L.
Abstract: Differences in synchronous movement between the trunk and lower limb during lifting have been reported in chronic low back pain (CLBP) patients compared to healthy people. However, the relationship between movement coordination and disability in CLBP patients has not been investigated. A cross-sectional study was conducted to compare regional lumbar and lower limb coordination between CLBP (n = 43) and control (n = 29) groups. The CLBP group was divided into high- and low-disability groups based on their Oswestry Disability Index (ODI) score. The mean absolute relative phase (MARP) angles and mean deviation phase (DP) between the (1) lumbar spine and hip, and (2) hip and knee were measured. The relationship between MARP angle and DP and ODI were investigated using linear regression. The higher-disability CLBP group demonstrated significantly greater lumbar-hip MARP angles than the lower-disability CLBP group (mean difference = 12.97, % difference = 36, p = 0.041, 95% CI [2.97, 22.98]). The higher-disability CLBP group demonstrated significantly smaller hip-knee DP than controls (mean difference = 0.11, % difference = 76, p = 0.011, 95% CI [0.03, 0.19]). There were no significant differences in lumbar-hip and hip-knee MARP and DP between the lower-disability CLBP and control groups. Lumbar-hip MARP was positively associated with ODI (R 2 = 0.092, β = 0.30, p = 0.048). High-disability CLBP patients demonstrated decreased lumbar-hip movement coordination and stiffer hip-knee movement during lifting than low-disability CLBP patients and healthy controls.